Depression and Other Mental Health Disorders Among Athletes with Injuries: Challenges in Diagnosis, Treatment, and Rehabilitation - Dzieciatkowska, Marta; Horwat, Paulina; Pierudzka , Weronika; Szymanska, Anita; Mariowska , Agnieszka (Journal of Education, Health and Sport, 2025)
Athletes are often praised for their physical resilience, but they are also vulnerable to mental health challenges, particularly following an injury. Musculoskeletal injuries, the most common type in sports, not only increase the risk of further harm but also impede recovery, contribute to depression or other mental health disorders, and adversely affect athletic performance. Emotional reactions such as sadness, isolation, anger, and a loss of motivation can exacerbate mental health issues. At the same time, psychological stress, fear of reinjury, and uncertainty about recovery timelines create a cycle of distress that hinders both physical and mental healing. Although emotional responses to injury are regular, prolonged or intense reactions can lead to more serious conditions, including depression, anxiety, eating disorders, or substance abuse. Given the critical link between mental health and recovery, it is essential to address the mental well-being of athletes during their rehabilitation process. Early intervention and psychological strategies are key in improving recovery outcomes and supporting overall mental health. However, many athletes face barriers to seeking help, such as stigma and lack of awareness. Practical strategies for supporting mental health during rehabilitation include mental health education, early screening, interpersonal therapy, cognitive-behavioral therapy, mindfulness practices, and visualization techniques. Integrating these approaches into rehabilitation plans enables athletes better to manage the mental and physical challenges of recovery. A collaborative approach involving coaches, healthcare providers, and mental health professionals is essential to ensuring comprehensive support for athletes' well-being throughout rehabilitation. By addressing the physical and psychological aspects of recovery, athletes can return to their sport with improved resilience and confidence.